Ex vivo canine vocal fold lamina propria rehydration after varying dehydration levels - Hanson, Kevin P. (2010)
OBJECTIVES: To examine the recoverability of canine vocal fold lamina propria upon rehydration from varying dehydration levels. STUDY DESIGN: Open controlled experimental trial METHODS: The vocal fold lamina propria was excised en block using a scalpel from ten canine larynges, providing twenty tissue samples. The initial volume of each sample was measured. Ten samples were dehydrated to 30% by mass, and the other ten samples to 70%. Each sample was rehydrated in 0.9% saline until the mass stabilized. The liquid mass and volume fractions, liquid:solid mass and volume ratios, and the fractions of the original tissue masses and volumes were calculated. RESULTS: All calculated parameters were significantly different between 30% and 70% dehydration recovery, with all parameters lesser in the 70% dehydration treatment group. Half of the tissue samples subjected to 30% dehydration fully recovered to their original volumes, while only 1 of the 10 samples subjected to 70% dehydration fully recovered its volume. CONCLUSIONS: The level of attainable rehydration recovery of vocal fold lamina propria tissue in an ex vivo setting depends on the level of dehydration. The results correspond with the biphasic theory and may be used to help model the biomechanical and physiological properties of vocal fold lamina propria tissue during rehydration.